2017
DOI: 10.1093/gastro/gox002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hypoalbuminemia is associated with an increased risk for intra-abdominal septic complications after primary anastomosis for Crohn’s disease

Abstract: ObjectiveThe aim of this study was to evaluate the impact of preoperative hypoalbuminemia on the development of intra-abdominal septic complications (IASCs) after primary anastomosis for patients with Crohn’s disease (CD).MethodsAll CD patients undergoing bowel resection with a primary anastomosis during the study period from 2007 to 2015 were enrolled. The association of preoperative hypoalbuminemia (<30 g/L) with the risk for IASCs were assessed using both univariate and multivariate analyses.ResultsA total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…In inflammatory bowel disease with chronic inflammation, surgical stress increases the risk of postoperative sepsis if preoperative serum albumin levels are low [ 128 , 129 ]. Similarly, in hemodialysis, hypoalbuminemia affects the risk of sepsis in catheter-related bloodstream infection [ 130 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…In inflammatory bowel disease with chronic inflammation, surgical stress increases the risk of postoperative sepsis if preoperative serum albumin levels are low [ 128 , 129 ]. Similarly, in hemodialysis, hypoalbuminemia affects the risk of sepsis in catheter-related bloodstream infection [ 130 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…6 Many studies found that albumin levels less than 3 g/dL were associated with post-operative complications. 7,8 Albumin level less than 3.5 g/dL was associated with respiratory complications (pneumonia in 30 days post-operative, delayed ventilator weaning, and reintubation), surgical site infection, dehiscence, longer hospitalization period, and increasing one-year mortality risk. [9][10][11] Patients underwent abdominal surgery and had hypoalbuminemia were at risk of post-operative complications and higher risk of mortality.…”
mentioning
confidence: 99%
“…[9][10][11] Patients underwent abdominal surgery and had hypoalbuminemia were at risk of post-operative complications and higher risk of mortality. [8][9][10][11] However, the prognostic role of albumin level in children with abdominal surgery remains unclear. Therefore, we aim to investigate the impact of albumin levels on clinical outcomes related to the complications in children with abdominal surgery.…”
mentioning
confidence: 99%
“…The incidence of preoperative hypoalbuminemia varies between studies. In surgical patients with Crohn's disease, it was shown in 11.7% of patients (Liu et al 2017). In colon cancer patients, it has been shown that 14.5% of patients had preoperative hypoalbuminemia (Haskins et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In surgical patients with Crohn's disease, preoperative hypoalbuminemia (i.e. <3.5gdL À1 ) significantly increased the risk of intra-abdominal septic complications (OR 4.67, 95% CI 1.28-17.04, p ¼ 0.02) (Liu et al 2017). In surgical patients with inflammatory bowel disease, modest and severe hypoalbuminemia in the preoperative period was associated with increased mortality, whereas severe preoperative hypoalbuminemia was associated with septic complications (Nguyen et al 2019).…”
Section: Discussionmentioning
confidence: 99%